Thermally driven directional free-radical polymerization in confined channels. Issue 8 (23rd January 2019) - Datta, Preeta; Efimenko, Kirill; Genzer, Jan
Abstract : We report on the formation of poly(acrylamide) (PAAm) with a relatively-narrow molecular weight distribution (MWD) by means of thermally-driven directional free-radical polymerization carried out in polymerization chambers featuring two parallel glass walls separated by various distances, ranging from sub-millimeter to a few millimeters. Abstract : We report on the formation of poly(acrylamide) (PAAm) with a relatively-narrow molecular weight distribution (MWD) by means of thermally-driven directional free-radical polymerization carried out in polymerization chambers featuring two parallel glass walls separated by various distances, ranging from sub-millimeter to a few millimeters. Using this experimental setup, in conjunction with size exclusion chromatography and peak fitting of MWD profiles of the resulting PAAm, we decouple two simultaneous modes of AAm polymerization reaction mechanisms, i.e., thermal and monomer-initiated decompositions.